Transparency and Traceability of Congressional Earmarks: a System for Monitoring and Analyzing Public Data - Pinto, Fernando Antonio Dantas Gomes; Pessanha, Jônatas Tavares; Bondarovsky, Bruno; Lifschitz, Sérgio; Haeusler, Edward Hermann (Anais do Latin American Symposium on Digital Government (LASDiGov); 2025: Anais do XIII Latin American Symposium on Digital Government, 2025)
Transparency in public funds is essential for oversight and social control. However, some current monitoring solutions for Congressional Earmarks are incomplete. Official government sources are distributed across multiple endpoints, making data extraction challenging and creating user uncertainties. In addition, other initiatives are limited to specific types of congressional earmarks, failing to provide a comprehensive view of the process. This paper presents the development of a system capable of tracking the entire lifecycle of congressional earmarks, from proposal to payment. The solution was made with a relational database, allowing structured queries to identify authors, recipients, amounts, and congressional earmarks locations (municipal, state, and regional). Additionally, the system integrates Business Intelligence (BI) tools to generate interactive analytical views, facilitating data comprehension and supporting decision-making. With a clear and user-friendly interface, the platform improves transparency and is essential for researchers, journalists, and citizens interested in monitoring budget allocations.